ความต้องการของประชาชนในภาคใต้ต่อบริการสุขภาพที่บ้าน - ศรัณยา บุนนาค (มหาวิทยาลัยสงขลานครินทร์, 2022)
Homne health care services focuses on providing services to patients based on the same health program provided in general hospitals. Instead of traveling to a hospital, patients will find it more convenient to be treated at their own places. The purposes of this research were to study the need to use home health care servises, willingness to pay, satisfaction towards the use of health services and behavior in choosing health services provided by state or private hospitals. Based on Multi-Stage Sampling of 1000 sampling population through the interview conducted during March-May, 2005, it was found that the majority of the interviewees were Buddhist males with average age of 47.34 years, and 40.2% have obtained tertiary education or higher level. Meanwhile, almost half of the sampling population has run his own business or has been working as government officials, Is, with average family income of 41,603 baht/mondh. Moreover, there was a high risk of health among family members with 39.1% of sampling popalation being exposed to smoking famaly members, 41.6% comsuming alcoholic beverages, and 24.6% of the sampling group did not do any exercises. Further, 58.5% slept less than 8 hours; 63.8%s of sampling population has mostly relied on the health insurance card (30 baht) while 35.4% was on state enterprise welfare and 28.8% on social insurance respectively. The sampling population and family members were mostly suffering from the first three ailments: respiratory system (14.1%), endocrine (10.6%) and vascular and bload system (10.2%) respectively. All disabled family members and the addicts need to continue health care at home, including 83.3% of people with malnourished condition, 80% of cancer patients and 70% of people suffering from chronic headache. Meanwhile, 27.5% of sampling group's family members need to take regular medication with the average payment of 1,194 baht/month, and there were 45.4% of the sampling group with the family members whose medication bills, with the average payment of 913 baht/month, could not be reimbursed ed. Except Yala province, the sampling population in Songkhla, Nakhon-Srithammarat, Surathani and Patthalung were much more satisfied with health services provided by the private hospitals than those offered by the state hospitals, and about 76.9% of health insurance 30-baht card holders have showed satisfaction on both the obtained quality and health services. In addition, home health care services required by the sampling group were general health checkups such as blood checking. ECG, family planning consultation, infertility consultation, pregnancy checking. vaccination, general health services for children, health services for patients with the age between 13-55 years, disbetes checking, health services for the elderly with the age more than 55 years up and an ernergency car service. The sampling group was willing to pay more, with the average increase in payment of 22.15% for the same account of health service fee charged by the hospital. Moreover, they were willing to pay extra 500 baht/time in case there were home health services provided by nurses or health personnel, and 30.6% of the sampling groups were willing to pay for additional service charge of 2000 baht/time if doctors or nurses visited and provided health services directly at their places.